Immunohistochemical localisation of d-β-aspartic acid in pingueculae. Issue 7 (9th March 2009) - Kaji, Y; Oshika, T; Okamoto, F; Fujii, N
Abstract : Background: d -β-Aspartic acid residues, which are biologically uncommon, have been reported to accumulate in various proteins of the living body with age. In the present study, d -β-aspartic acid-containing proteins were found to be localised in pingueculae, which represent one of the most prominent age-related ocular changes. Methods: Surgical specimens of conjunctivae with or without pingueculae were obtained from eight patients. Immunohistochemical localisation of d -β-aspartic acid-containing proteins was performed using a polyclonal antibody against d -β-aspartic acid-containing peptides. Results: Strong immunoreactivity to d -β-aspartic acid-containing peptides was detected in the subepithelial amorphous materials of all surgical specimens with pingueculae. In contrast, no immunoreactivity to d -β-aspartic acid-containing peptides was detected in the specimens without pingueculae. Conclusions: Pingueculae are thought to be aggregates of proteins that contain d -β-aspartic acid residues. It is known that the conversion of l - to d -aspartyl residues is accelerated by ultraviolet irradiation. In addition, d -β-aspartic acid-containing proteins, in general, tend to aggregate with each other and accumulate in the tissues. These facts indicate that ultraviolet irradiation-induced racemisation of aspartic acid is closely related to the development of pingueculae.